The UMLS Semantic Network - McCray, Alexa T. (1989)
The UMLS network of semantic types is one component of NLM's evolving Unified Medical Language System. This paper discusses the role of the semantic network in the overall system, then describes the evolution and current status of the network, and, finally, concludes with a discussion of plans for further development.